2020
DOI: 10.1177/2632666320957854
|View full text |Cite
|
Sign up to set email alerts
|

“Changing the channel”: Hybrid masculinity in a men’s prison

Abstract: Penological literature has focused extensively, and often exclusively, on the “hypermasculine” nature of men’s prisons. A separate and relatively recent body of sociological research has explored “hybrid masculinities,” whereby (usually privileged) men selectively enact traits conventionally associated with subordinate masculinities and even femininities. In this article, I draw on 24 in-depth interviews with incarcerated men to argue that these men construct hybrid masculinities in response to their feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The prison environment assumes a set of prescriptive norms that exaggerate traditional male attributes and encourage displays of domination, bravery, competition, violence, and aggression (Ricciardelli et al, 2015). Men’s adoption of hypermasculinity in prison settings is not simply a legitimate response to a dangerous living environment (de Vigiani, 2012), but represents an effort to cope with the destruction of the self that prison entry inevitably entails (Umamaheswar, 2020). When a man enters prison, his pre-prison identity is fundamentally altered (Asencio & Burke, 2011; Umamaheswar, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prison environment assumes a set of prescriptive norms that exaggerate traditional male attributes and encourage displays of domination, bravery, competition, violence, and aggression (Ricciardelli et al, 2015). Men’s adoption of hypermasculinity in prison settings is not simply a legitimate response to a dangerous living environment (de Vigiani, 2012), but represents an effort to cope with the destruction of the self that prison entry inevitably entails (Umamaheswar, 2020). When a man enters prison, his pre-prison identity is fundamentally altered (Asencio & Burke, 2011; Umamaheswar, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, the few studies that have evaluated the success of therapeutic programs in redefining men’s sense of masculinity have shown that there is reason for optimism (Fournier, 2016; Karp, 2010). Nevertheless, research critiquing the notion that men are one-dimensionally “hypermasculine” has also shown that men must adapt their masculinities to different settings in prison to cope with hypermasculinity (Crewe et al, 2014; Umamaheswar, 2020b; Warr, 2020). Feminist family therapists should thus be thoughtful when naming and describing their therapeutic programs to potential clients who may be stigmatized and perceived as weak for being involved in “feminist” therapy.…”
Section: Clinical Implications and Future Directions: Developing Gend...mentioning
confidence: 99%
“…Masculinities are socially constructed and fluid, which means that their meanings are derived from shared understandings that evolve over social and historical contexts (Adams & Coltrane, 2005;Connell, 1998). Criminological and penological research has exhaustively demonstrated the salience of men's constructions of masculinity in their offending patterns (Messerschmidt, 1993(Messerschmidt, , 2005Rios, 2009) as well as their prison lives (Sabo et al, 2001;Sykes, 1958;Umamaheswar, 2020b). Research in this area has historically relied on the theoretical framework of "hegemonic masculinity" -the legitimized and idealized model of masculinity that valorizes aggression, competition, dominance, and strength (Connell & Messerschmidt, 2005).…”
Section: Prison Masculinitiesmentioning
confidence: 99%
See 2 more Smart Citations